1982
DOI: 10.1016/0013-4686(82)85065-2
|View full text |Cite
|
Sign up to set email alerts
|

Comportement electrochimique anodique de divers neuroleptiques en milieu aqueux et non-aqueux

Abstract: Reçu le 2 juillet 1981) Résumé-Les propriétés électrochimiques d'une série de neuroleptiques possédant en commun un hétérocycle central à 7 atomes avec un groupement amidine semi-cyclique, en milieu aqueux et non-aqueux ont été examinées à l'aide de la voltampérométrie sur électrodes à disque de platine poli, de carbone vitreux et de pâte de carbone, de la voltammétrie cyclique, et de la coulométrie à potentiel contrôlé. Le comportement oxydatif des trois molécules envisagées en milieu neutre aqueux et non-aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The electrochemical oxidation [17,19] and réduction [18.20] of the molécules have been studied quite extensively. Table 1 contains a summary of the mechanisms proposed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical oxidation [17,19] and réduction [18.20] of the molécules have been studied quite extensively. Table 1 contains a summary of the mechanisms proposed.…”
Section: Resultsmentioning
confidence: 99%
“…The equipment for thin-layer spectroelectrochemistry has been described elsewhere [17][18][19][20][21].…”
Section: Ismentioning
confidence: 99%
“…In particular, d 10 metal complexes have attracted much interest in recent years, not only because of their interesting structures but also because of their photoluminescence properties [12,13]. Although there have been several reports on the electrochemical behavior of piperazine molecules [14][15][16][17], study of their anodic oxidation in a coordinated polymer has not been reported. In this paper we report the preparation, crystal structure, IR spectroscopy, thermal stability, and the luminescence and electrochemical properties of a novel cadmium coordination polymer [Cd(pipH)(Cl)(l-Cl) 2 ] n ÁnH 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical characterization of the process was done by using chronocoulometry, voltammetry and exhaustive coulometry 6, 7. The oxidation involved the aniline N atom and resulted to be a two‐step one‐electron reversible process, coupled with irreversible chemical reactions (EC mechanism).…”
Section: Introductionmentioning
confidence: 99%